Hyperplasia of thymic gland - Lee, Y.M.; Koh, M.T.; Omar, A.; Majid, A. (Stamford Publishing Pte Ltd / Singapore Medical Association, 1996)
Hyperplasia of the thymus is the most common anterior mediastinal mass in infants. It is however exceedingly difficult to evaluate by the weight of the gland as it continues to grow after birth until puberty and thereafter undergoes progressive atrophy. It normally maintains most of the radiographic characteristics of the normal thymus. Massive thymic hyperplasia, a rare variant of true thymic hyperplasia is extremely rare during the first two decades of life and clinically can cause mediastinal compression or acute and recurrent pulmonary infection. Two such cases are reported and the clinico-pathology is briefly described and discussed.